Integrative-Holistic Islamic Curriculum Framework: A Conceptual Model for Contemporary Curriculum Development - Sri Murhayati; Nurhasnawati; Eliza Putri Ardiah; Nurul Habibah Arfizeah; Hafizah (JEICI - Journal of Education and Islamic Contemporary Issue, 2026)
This study develops the Integrative–Holistic Islamic Curriculum Framework (IHICF) as a conceptual model to address persistent fragmentation in Islamic Religious Education (PAI) and its limited alignment with contemporary educational demands. The separation between religious knowledge and modern scientific disciplines, along with instructional practices dominated by memorization, has reduced the relevance of PAI to twenty-first-century competencies such as digital literacy, critical thinking, collaboration, and ethical reasoning. Using a qualitative library research approach, this study analyzes literature published between 2020 and 2025 through systematic selection, open coding, thematic synthesis, and conceptual triangulation. The analysis yields four pillars of the IHICF: internal integration across PAI subjects; external integration with modern sciences and social realities; holistic and adaptive learner development; and operational mechanisms involving curriculum planning, teacher capacity, and authentic assessment. The findings indicate that IHICF offers a coherent and applicable curriculum model that bridges Islamic values with contemporary learning needs. It provides structured pathways for thematic instruction, value-based projects, collaborative teaching, and meaningful digital integration. The framework contributes to PAI renewal by supporting learners' ethical grounding, intellectual competence, and social responsiveness.